Co-feeding of live feed and inert diet from first-feeding affects Artemia lipid digestibility and retention in Senegalese sole (Solea senegalensis) larvae - Mai, Monica Giacometti; Engrola, Sofia; Morais, Sofia; Portella, Maria Celia [UNESP]; Verani, Jose Roberto; Dinis, Maria Teresa; Conceicao, Luis E. C. (Elsevier B.V., 2009)
The present study intended to evaluate the effects of early introduction of inert diet in lipid digestibility and metabolism of sole, while larval feed intake, growth and survival were also monitored. Solea senegalensis larvae were reared on a standard live feed regime (ST) and co-feeding regime with inert diet (Art R) Trials using sole larvae fed with Artemia enriched with two different lipid emulsions. containing glycerol tri [1-(14)C] oleate (TAG) and L-3-phosphatidylcholine-1,2-di-[1-(14)C] oleoyl (PL), were performed at 9 and 17 days after hatching (DAH) to study lipid utilization Co-feeding did not affect sole survival rates (ST 59.1 +/- 15.9%: Art R 69.56 +/- 9.3%), but was reflected in significantly smaller final weight at 16 DAH (ST 0.71 +/- 0.20: Art R 0.48 +/- 0.14 mg). Higher feed intake was observed in sole larvae fed on Artenna enriched with labeled PL at 9 DAH but not at 17 DAH. At 17 DAH, the smaller larvae (Art R treatment) ingested proportionally more Artemia in weight percentage, independently of enrichment. At 9 DAH lipid digestibility was equal among treatments and higher than 90%, while at 17 DAH it was higher in ST treatment (around 73%) compared to the Art R group (around 66%). Lipid retention efficiency at 9 DAH was higher in the Art R treatment, reaching values of 50%, while these values almost duplicated at 17 DAH. ranging tip to 80% in both treatments without significant differences. These results show that co-feeding of live feed and inert diet from first-feeding in Senegalese sole has a toll in terms of growth and lipid digestibility but does not seem to compromise lipid metabolic utilization. (C) 2009 Elsevier B V. All rights reserved.
Keywords: Solea senegalensis; Weaning; Lipid metabolism; Digestibility; Feed Intake; Metamorphosis